Niemiecka scena polityczna po wyborach w 1994 i 1998 roku. Kierunki ewolucji = German political scene following the 1994 and 1998 elections. The directions of the evolution - Flakowski, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is devoted to the presentation of the dynamism of changes observable as a result of the struggle for power in the German political system during Bundestag deputies elections in the years 1994 and 1998. In order to describe precisely the regularities of the conduct of election campaigns in the Federal Republic of Germany, the article presents some definitions of the elements which set the research 'frames' of the German political scenes. The author discusses the Bundestag election system, the idea of a party and the party system as well as basic concepts of political marketing.
Keywords: Niemcy; wybory; polityka wewnętrzna